Pelatihan Pengolahan Sampah Limbah Rumah Tangga dalam Mendukung Green Economy: Household Waste Processing Training in Supporting the Green Economy - Mufriantie, Fithri; Ibrahim, Jabal Tarik; Amir, Nur Ocvanny (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service aims to provide education/knowledge to partners about sorting organic and inorganic waste as well as providing skills in the form of training in organic and inorganic waste management. The methods or stages carried out consist of socialization/counseling, training, application of technology, evaluation of work programs, and sustainability of programs that have been carried out. Community service activities are carried out at PKK Kendalsari Tulusrejo Lowokwaru, Malang City. The training carried out received a positive response and enthusiasm from partners and resulted in processing organic waste into ecoenzyme products from fruit peels and processing inorganic waste into various kinds of handicrafts such as key chains from bottle caps, and pencil baskets from plastic straws.